Cognitive Value and Numerical Accuracy in Geocomputation: Choosing a Method to Compute the Log‐Jacobian Term. Issue 3 (July 2014) - Smirnov, Oleg A.
<x xml:space="preserve">Abstract</x> This article addresses the importance of cognitive value, numerical accuracy, and technical feasibility for geospatial models and methods. Researchers pursue large spatial data in an analysis to improve the statistical efficiency of parameter estimates and the cognitive value of the results. The critical requirement for this strategy is the availability of numerically accurate computational methods, without which parameter estimates lose their cognitive value. This article illustrates the relationship between cognitive value and numerical accuracy by establishing properties of popular polynomial schemes for approximating the log‐Jacobian term in spatial autoregressive models. It shows that numerical inaccuracies might be more misleading than is commonly assumed. En este artículo se aborda la importancia del valor cognitivo, la precisión numérica, y la viabilidad técnica de los modelos y métodos geoespaciales. Los investigadores interesados en análisis espacial tienden a preferir el uso de bases de datos de gran tamaño con el fin de mejorar la eficiencia estadística de sus estimaciones de parámetros y el valor cognitivo de los resultados. El requisito crítico para esta estrategia es la disponibilidad de métodos computacionales numéricamente precisos, sin los cuales las estimaciones de parámetros pierden su valor cognitivo. En este artículo se ilustra la relación entre el valor cognitivo y precisión numérica mediante la determinante jacobiano tipo log en modelos espaciales autorregresivos (spatial autorregresive models‐SAR). El estudio demuestra que las imprecisiones numéricas pueden ser más engañosas de lo que se asume comúnmente. 本文描述了地理空间模型和方法中认知价值、数值精度、技术可行性的重要性。研究者一般倾向于通过追求大规模空间数据，来提升参数估计的统计有效性和结果的认知价值。这一策略的关键是有实用的精确数值计算方法，否则参数估计将失去其认知价值。本文通过建立普遍使用的多项式方案来逼近空间自回归（SAR）模型中的Log‐Jacobian，从而说明认知价值和数值精度间的关系。结果表明数值不确定性可能比通常假设的误导性更大。